Polyimide-Based Membrane Materials for CO2 Separation: A Comparison of Segmented and Aromatic (Co)polyimides - Andrzej Jankowski; Eugenia Grabiec; Klaudia Nocoń-Szmajda; Andrzej Marcinkowski; Henryk Janeczek; Aleksandra Wolińska-Grabczyk (Membranes, 2021)
A series of new poly(ethylene oxide) (PEO)-based copolyimides varying in hard segment structure are reported in this work as CO2 selective separation membranes. Their structural diversity was achieved by using different aromatic dianhydrides (4,4′-oxydiphthalic anhydride (ODPA), 4,4’-(hexafluoroisopropylidene)diphthalic anhydride (6FDA)) and diamines (4,4′-oxydianiline (ODA), 4,4′-(4,4′-isopropylidene-diphenyl-1,1′- diyldioxy)dianiline (IPrDA), 2,3,5,6-tetramethyl-1,4-phenylenediamine (4MPD)), while keeping the content of PEO (2000 g/mol) constant (around 50%). To get a better insight into the effects of hard segment structure on gas transport properties, a series of aromatic polyimides with the same chemistry was also studied. Both series of polymers were characterized by 1HNMR, FTIR, WAXD, DSC, TGA, and AFM. Permeabilities for pure He, O2, N2, and CO2 were determined at 6 bar and at 30 °C, and for CO2 for pressures ranging from 1 to 10 bar. The results show that OPDA-ODA-PEO is the most permeable copolyimide, with CO2 permeability of 52 Barrer and CO2/N2 selectivity of 63, in contrast to its fully aromatic analogue, which was the least permeable among polyimides. 6FDA-4MPD-PEO ranks second, with a two times lower CO2 permeability and slightly lower selectivity, although 6FDA-4MPD was over 900 times more permeable than OPDA-ODA. As an explanation, partial filling of hard domain free voids by PEO segments and imperfect phase separation were proposed.